Permian palynomorphs from the number 5 seam, Ecca Group, Witbank/Highveld coalfields, South Africa - Aitken, G A (Bernard Price Institute for Palaeontological Research, 1994)
A palynological study of the number 5 seam in the Ecca group has yielded a wide variety of miospores, with a lateral and vertical consistency in their relative abundance, diversity and composition. Striate bisaccate pollen genera predominate, particularly Protohaploxypinus Samoilovich emend. Morbey 1975, Striatopodocarpites Zoricheva & Sedova ex Sedova emend. Hart 1964 and Weylandites Bharadwaj & Srivastava 1969. On a regional scale the number 5 seam palynomorphs correlate both quantitatively and qualitatively with Biozone F of MacRae (1988) from the Waterberg and Pafuri coal-bearing basins, and Hammanskraal plant locality. Broad palaeoenvironmental inferences drawn from both the palynology and sedimentology of this seam, support a flood plain setting, comprising shallow wide open pans and peat swamps interspersed with wide water-logged mud flats . The surrounding highlands would have been forested mostly by plants adapted to wind dispersal with colonisation of the levees and margins of smaIl ponds by spore producers. The age of the number 5 seam is tentatively suggested as Guadalupian, which in turn is equated with the Tatarian (European Standard usage); Midian to Dzhulfian (Tethys usage).
Keywords: ecca; Karoo; palynology; permian; biostratigraphy